La Facultad de Contaduría Pública de la Universidad Santo Tomás: 40 años construyendo verdad con fe pública (2012)
This paper presents an overview of the most important aspects that have made history in the Faculty of Public Accountancy at Universidad Santo Tomás, in its  40 years of existence. The purpose of this paper, in agreement with the research project that gave rise to it, is to share with the society, especially with the students and with those who today proudly practice as Tomasino Public Accountants, the historical memory of a faculty that has contributed greatly to the formation of accountants, as well as to the consolidation and development of the accounting discipline in Colombia.The content of the document presents, rst, the context and the scenario that led to the creation of the Faculty of Public Accountancy at Universidad Santo Tomas, and then, describes specic elements regarding its origin and development. Here, diferent aspects of the academic and administrative structures, events, awards, and leaders, including directors, teachers, students and graduates, are also exposed.Thus, this document becomes asocialization instrument of the history of the Faculty of Public Accountancy at Universidad Santo Tomás, in order to identify its origins, its leaders, its development and its acknowledgments, which together have enabled to position the Faculty as one of the most important of the country.